2012
DOI: 10.1108/09578231211223347
|View full text |Cite
|
Sign up to set email alerts
|

Communities of practice in the school workplace

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
2
14
0
4
Order By: Relevance
“…Wasko, Teigland and Faraj () reported that for this reason several researchers have opted not to use the term CoP and treated it with caution because of the limited clarity on it. The terms network of practice, network of improvement or network of design have instead been used depending on the specific purpose of the created group (Brouwer, Brekelmans, Nieuwenhuis & Simons, ).…”
Section: Discussionmentioning
confidence: 99%
“…Wasko, Teigland and Faraj () reported that for this reason several researchers have opted not to use the term CoP and treated it with caution because of the limited clarity on it. The terms network of practice, network of improvement or network of design have instead been used depending on the specific purpose of the created group (Brouwer, Brekelmans, Nieuwenhuis & Simons, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, when there is a dysfunction of such relationships, the school leader is likely to fail. Novice school heads may suffer from professional isolation, whereby they do not get any support and collaboration from other school stakeholders, and therefore they become depressed [34]. According to Kelly and Saunders [35], novice school heads experience professional loneliness during the first three years of headship because of their lack of experience and incompetency to do networking with others.…”
Section:  Issn: 2089-9823mentioning
confidence: 99%
“…The concept of community has been well-researched in education framed within perspectives of ethics, professionalism, inquiry, inclusion, among others (Brouwer et al, 2012;Furman, 2004;Little, 1990;Louis & Marks, 1998;Redding & Thomas, 2001;Strike, 2007;Wenger, 1998). From a sociological perspective, researchers indicate that we often build community in schools because we are drawn to work and live together in ways that help us to make deeper meaning of our lives (Block, 2009;Brown & Hannic, 2008;Rifkin, 2011;Vanier, 2003).…”
Section: Adaptive Communitymentioning
confidence: 99%